Irony in World Dramas - Khamdamovna, Mavlonova Ugiloy; Rasuljonovna, Ergasheva Fotima (Researchparks Publishing, 2023)
The playwright, like an actor, loses the fate of the characters on himself, lives their conflicts. This is not about the methods of creating the play, there are various ways, but about the essence of the structural relations of the drama. The communication of the author with the viewer - reader remains dramatic in nature. Of course, the immediacy of stage relations in the literary version is reproduced indirectly, metaphorically, and this in its own way affects the movement of dramatic forms.